Long-Term Follow-Up of Patients with Malignant Pedunculated Colon Polyps after Colonoscopic Polypectomy - Hugh James Freeman (Canadian Journal of Gastroenterology)
BACKGROUND: Previously published studies have suggested that patients with resected colon cancer have an increased risk for early metachronous colon cancer. Current screening guidelines recommend intense surveillance by colonoscopy for the initial five years after the initial colon cancer has been resected. Information regarding endoscopically removed malignant polyps is limited.